After the "Socialist Spring" Collectivisation and Economic Transformation in the GDR - Last, George (Monographs in German History, 2009)
Drawing on a broad range of archival material from state and SED party sources as well as Stasi files and individual farm records along with some oral history interviews, this book provides a thorough investigation of the transformation of the rural sector from a range of perspectives. Focusing on the region of Bezirk Erfurt, the author examines on the one hand how East Germans responded to the end of private farming by resisting, manipulating but also participating in the new system of rural organization. However, he also shows how the regime sought via its representatives to implement its aims with a combination of compromise and material incentive as well as administrative pressure and other more draconian measures. The reader thus gains valuable insight into the processes by which the SED regime attained stability in the 1970s and yet was increasingly vulnerable to growing popular dissatisfaction and economic stagnation and decline in the 1980s, leading to its eventual collapse.